Guidelines and best practices for assessing young children remotely - McRoy, Kyla Z.; Skibbe, Lori E.; Ahmed, Sammy F.; Tatar, Burcu H. (Frontiers in Public Health, 2024)
Given the recent rise in the use of remote assessments to collect data from young children, researchers and practitioners would benefit from guidance on best practices within the field. Based on our experiences with assessing over 600 preschoolers remotely, our research team provides a set of main principles to guide professionals to successfully create and operationalize systems for remote assessment. Guidelines include detailed information about how to choose a technology platform, select and use online assessments, and how to adapt traditional tasks for remote use. We also note the challenges inherent in using certain types of tasks, provide tips for scheduling remote sessions, and offer advice for how to promote children’s engagement throughout the assessment process.